(untitled) (Anwer Khan Modern Medical College Journal, 2011)
This was a descriptive type of cross-sectional study conducted in three villages of Shahjadpur Upazila in the month of October, 2010 among the rural households who visited medical practioners for the last three months. It was aimed to determine the socio-demographic characteristics of the respondents, availability of prescriptions, diagnosis written, number of drugs and antibiotics including its duration written within the prescription. It also determines the duration of antibiotic, dose and course including the advices on life style mentioned in the prescription in particular. It was revealed from the findings that 73.27% respondents were within 15-44 years of age with mean age 34.8 years and SD ± 13.09. In this study 68% respondents were attended doctors chamber during last three months, of them prescriptions were available to 57% respondents for investigation according to the stated objectives. Number of drugs in one prescription was 3-5 in 77% prescriptions. On the other hand 58% prescriptions were having 1-2 antibiotics. However, dose of antibiotics were not mentioned to about 31% prescriptions only. The duration 3-6 days of antibiotics was mentioned only about 23% prescriptions. Advices on life style and diagnosis were mentioned only to 32 and 52% prescriptions respectively. The investigation also revealed the qualification of prescribers and found 22.64% prescriptions by non-qualified doctors. The finding of the study can be a basis to take appropriate measures among prescribers in the locality towards maintaining the standard and rationality of prescriptions for the patients seeking drug treatment for any type of ailments. It will also help practitioners to provide a rational prescription to the consumers in regards to the number of drugs as well as clarity of instruction of its uses in deed. Key Words: Prescription; Pattern; Rural Household DOI: 10.3329/akmmcj.v1i2.7459 Anwer Khan Modern Medical College Journal 2010; 1(2): 12-16